pengaruh suhu blanching terhadap sifat fisik dan kimia Frozen food sayur terung (solanum melongna L) dan pengamatan penyimpanan - Karmila, Karmila; Tahir, Muh; Antuli, Zainudin (Jambura Journal of Food Technology, 2024)
Frozen Food is processed frozen instant food that is durable and easy to serve. Frozen food in Indonesia remains limited, while the consumers want practicality in processing food, especially vegetables. The present research aimed to determine the effect of blanching temperature on eggplant quality, namely vitamin C level and sugar content, as well as observe the changes in vitamin C level and sugar content after being stored for seven and 14 days. It applied a completely randomized design (CRD) with one factor, namely blanching temperature with three treatment levels: P1 (50°C), P2 (70°C), P3 (90°C), and each treatment was replicated three times. The results of Analysis of Variance (ANOVA) indicated that the value of vitamin C levels was not significant (p0.05), so it did not continue to Duncan's multiple range test. While the value of sugar content and organoleptic (color, aroma, texture, and taste) denoted a significant effect (p 0.05), so the Duncan's multiple range test signified a significant difference in all treatments. Besides, the descriptive storage observation on day 7 and day 14 was known to have decreased. In detail, the changes from the initial conditions of nutritional content in vitamin C and sugar content before and after being stored at cold temperatures (-20°C) are caused by the long storage time. Furthermore, the highest vitamin C was at the blanching temperature treatment of 2.12 ml/100, and the sugar contem was 10.33°Brix. At the same time, for the organoleptic, it was observable dat treatment 2 (50°C) was the most preferred by the panelists in color, aroma, texture and taste